E-022 Aneurysm neck healing following web-17 device implantation in an elastase induced rabbit model – histologic analysis. (22nd July 2018) - Dai, D; Ding, Y; Asnafi, S; Kallmes, D; Kadirvel, R
Abstract : Purpose: To classify the tissue patterns and cellular components at aneurysm neck following treatment with single layer (SL) and single layer sphere (SLS) WEB-17 devices in an elastase induced rabbit aneurysm model. Materials and methods: With institutional animal care and use committee approval, saccular aneurysms were created in 12 rabbits and treated with WEB-17 device (n=6 for SL, n=6 for SLS). The device-bearing aneurysms were harvested at 3 months after implantation. Following the macroscopic examination of aneurysm neck, a whole tissue mount en face staining of the wet specimen was performed for endothelial cells (CD-31) and smooth muscle cells (SMA). Tissue coverage presenting at the neck was scored as: 0) device struts were completely bare, with no tissue coverage; 1) tissue coverage is less than 50% of neck orifice; 2) the tissue coverage is 50%–75% of neck orifice; 3) tissue coverage is greater than 75% of neck orifice. Results: Three tissue patterns that appeared at the neck along with the device struts were discovered as 1) multiple, isolated, light brown-colored tissue islands of varied sizes (figure 1A), composed of inflammatory cells (figure 1D); 2) A confluent, brown-colored tissue patch (figure 1B) representing an incompletely organized thrombus containing scattered or diffused inflammatory cells and an acellular matrix (figure1E); and 3) A white, membrane-like tissue (figure 1C) that was positive for SMA and CD31 (figure 1F). The membrane-like issue was mainly located at the periphery, where it continued up the parent artery wall (figure 1C). Patterns 1 and 2 were seen in 6/6 (100%) for both of the SL and SLS groups. Membranous tissue was present in 4 of 6 (67%) for the SL group and 50% for the SLS group. The mean neck tissue coverage score was 1.5 and 1.8 for the SL and SLS groups, respectively. There was no statistical difference regarding the neck tissue coverage and rate of different tissue patterns between the two groups. Conclusion: The primary tissue that appeared at the aneurysm neck following WEB-17 treatment was thrombus and the adherence of clusters of inflammatory cells. The endothelialization mainly started from the periphery and was derived exclusively from the adjacent aneurysm/parent artery wall. Disclosures: D. Dai: None. Y. Ding: None. S. Asnafi: None. D. Kallmes: None. R. Kadirvel: None.